Inactivation of the Porphyromonas gingivalis fimA gene blocks periodontal damage in gnotobiotic rats - Malek, R; Fisher, J G; Caleca, A; Stinson, M; van Oss, C J; Lee, J Y; Cho, M I; Genco, R J; Evans, R T; Dyer, D W (Journal of bacteriology, 1994)
Fimbrial production by Porphyromonas gingivalis was inactivated by insertion-duplication mutagenesis, using the cloned gene for the P. gingivalis major fimbrial subunit protein, fimA. by several criteria, this insertion mutation rendered P. gingivalis unable to produce fimbrilin or an intact fimbrial structure. A nonfimbriated mutant, DPG3, hemagglutinated sheep erythrocytes normally and was unimpaired in the ability to coaggregate with Streptococcus gordonii G9B. The cell surface hydrophobicity of DPG3 was also unaffected by the loss of fimbriae. However, DPG3 was significantly less able to bind to saliva-coated hydroxyapatite than wild-type P. gingivalis 381. This suggested that P. gingivalis fimbriae are important for adherence of the organism to saliva-coated oral surfaces. Further, DPG3 was significantly less able to cause periodontal bone loss in a gnotobiotic rat model of periodontal disease. These observations are consistent with other data suggesting that P. gingivalis fimbriae play an important role in the pathogenesis of human periodontal disease.